Economic Analysis of Tef Yield Response to Different Sowing Methods and Seed Rates in Eastern Amhara, Ethiopia - Mekonnen Assefa; Tewabe Mehiret; Jhon Hardy Purba; Mesfin Bahta; Abere Haille (Universitas Panji Sakti, 2022)
The study was conducted in 2019/2020 for two years in Habru, Kobo, and Dawa Chefa districts of the Eastern Amhara with the main objectives of evaluating and validating the productivity, evaluating economic feasibility and selecting the best performing sowing method and seed rate of tef technologies under farmers condition. The districts were selected based on their representativeness for the growth of tef. Three treatments were used for the study namely row planting with 5kg.ha-1, row planting with 10kg.ha-1, and hand broadcasting methods. Tef (Zoble variety) was used for the study purpose. Based on the data obtained, the highest yield was obtained from the hand broadcasting (25kg.ha-1) and the lowest yield was from the row planting (5kg.ha-1). The mean yield of tef from the hand broadcasting (25kg.ha-1) was 16.5% higher than the row planting (5kg.ha-1). Similarly, the labor utilization has increased from hand broadcasting 25kg.ha-1to row planting of (5kg.ha-1) and 10kg.ha-1. The labor cost for row plantings of tef was also higher, whereas the hand broadcasting (25kg.ha-1) consumed the least labor. This study therefore has proved that hand broadcasting is both high yielder and economically feasible in the Eastern Amhara. In addition to this, the study suggests that there should be additional seed rate study on broadcasting In order to gain optimum tef yield with feasible economic advantage.